2021
DOI: 10.3892/etm.2021.10407
|View full text |Cite
|
Sign up to set email alerts
|

Expression of microRNA‑155‑5p in patients with refractory diabetic macular edema and its regulatory mechanism

Abstract: Diabetic macular edema (DME) is the main cause of visual impairment in diabetic patients, but its pathogenesis remains unclear. The purpose of the present study was to analyze the expression of microRNA (miR)-155-5p in patients with DME and its regulatory mechanism. A total of 72 patients diagnosed with DME and 17 with idiopathic macular hole (MH) were recruited. Among samples from patients with DME, 45 were DME and 27 were refractory DME, whereas patients with idiopathic MH served as the control group. Optica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Also, some of the DEmiRs are associated with diabetes complications, such as miR-133a-3p, which is associated with myocardial steatosis in T2D patients [76], and miR-129-2-3p [77] and miR-129-5p, which have been detected in T2D patients with macrovascular complications [78]. Furthermore, hsa-miR-155-5p is closely associated with diabetic macular edema (DME) [79]. Several upregulated miRNAs are detected to be associated with diabetic nephropathy (DN) patients such as, miR-372-3p [47], miR-548ah-3p, miR-760 [80], and miR-1269b [81].…”
Section: Discussionmentioning
confidence: 99%
“…Also, some of the DEmiRs are associated with diabetes complications, such as miR-133a-3p, which is associated with myocardial steatosis in T2D patients [76], and miR-129-2-3p [77] and miR-129-5p, which have been detected in T2D patients with macrovascular complications [78]. Furthermore, hsa-miR-155-5p is closely associated with diabetic macular edema (DME) [79]. Several upregulated miRNAs are detected to be associated with diabetic nephropathy (DN) patients such as, miR-372-3p [47], miR-548ah-3p, miR-760 [80], and miR-1269b [81].…”
Section: Discussionmentioning
confidence: 99%
“…During corneal wound healing, miR-155-5p reduces corneal epithelial permeability by reshaping tight epithelial junctions [ 38 ]. In diabetic macular edema, the inhibition of miR-155-5p expression downregulates cell proliferation, angiogenesis, and vascular endothelial growth factor levels [ 39 ]. These studies demonstrate that miR-155-5p can potentially be used as a biomarker for eye-related diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have shown that miR-155-5p plays an important role in the progression of diabetes. 50 , 51 It regulates the proliferation and angiogenesis of HRMECs (human retinal endothelial cells) and simultaneously affects the protein level of VEGF-A in HRMECs. Our previous findings indicated that SDMM capsules inhibit angiogenesis by suppressing the expression of the VEGF family, including VEGF-A.…”
Section: Discussionmentioning
confidence: 99%